2001
DOI: 10.1006/viro.2000.0804
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Dissection of the Membrane and RNP Binding Activities of Influenza Virus M1 Protein

Abstract: Spontaneous proteolysis of influenza virus M1 protein during crystallisation has defined an N-terminal domain of amino acids 1--164. Full-length M1, the N-terminal domain, and the C-terminal part of M1 (residues 165--252) were produced in Escherichia coli. In vitro tests showed that only full-length M1 and its N-terminal domain bind to negatively charged liposomes and that only full-length M1 and its C-terminal part bind to RNP. However, only full-length M1 had transcription inhibition activity. Several indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
153
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(163 citation statements)
references
References 28 publications
10
153
0
Order By: Relevance
“…However, the mechanism of M1-RNP interaction remains poorly understood. FLUA-M1 has been shown to bind NP (45), RNA (34,36), as well as RNP (4,35,46). In particular, Baudin et al demonstrated that it is the FLUA-M1 C domain, instead of the N domain, that is required for RNP binding (4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the mechanism of M1-RNP interaction remains poorly understood. FLUA-M1 has been shown to bind NP (45), RNA (34,36), as well as RNP (4,35,46). In particular, Baudin et al demonstrated that it is the FLUA-M1 C domain, instead of the N domain, that is required for RNP binding (4).…”
Section: Resultsmentioning
confidence: 99%
“…FLUA-M1 has been shown to bind NP (45), RNA (34,36), as well as RNP (4,35,46). In particular, Baudin et al demonstrated that it is the FLUA-M1 C domain, instead of the N domain, that is required for RNP binding (4). In a more recent study, it was shown that FLUA-M1 is SUMOylated at K242 from the C domain, and that the SUMOylation of M1 is required for the interaction between M1 and viral RNP (46).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5a and b). Previous studies have shown that expression of the M1 protein can repress transcriptional activity of RNPs (Baudin et al, 2001;Elster et al, 1997;Watanabe et al, 1996;Ye et al, 1987Ye et al, , 1989, which could be an explanation for the lower RNA levels observed.…”
Section: Expression Of the Viral Ns2/nep Protein Affects The Accumulamentioning
confidence: 86%